2009 2nd Conference on Human System Interactions 2009
DOI: 10.1109/hsi.2009.5090971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of personality and individual abilities on the sense of presence experienced in virtual environments

Abstract: There are few studies of the human factors involved in the engagement of presence. The present study aims to investigate the influence of five user characteristics -test anxiety, spatial intelligence, verbal intelligence, personality and computer experience -on the sense of presence in university students when exposed to virtual environments designed to assess their levels of test anxiety. This is the first study to investigate the influence of spatial intelligence on the sense of presence, and the first to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Unlike research with desktop systems, research with HMDs has failed to demonstrate the predicted relationship between spatial presence and spatial ability (Alsina-Jurnet & Gutiérrez-Maldonado 2010;Ling et al 2013). Alsina-Jurnet and Gutiérrez-Maldonado (2010) investigated a range of measures that may predict individual differences in experiences of presence.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike research with desktop systems, research with HMDs has failed to demonstrate the predicted relationship between spatial presence and spatial ability (Alsina-Jurnet & Gutiérrez-Maldonado 2010;Ling et al 2013). Alsina-Jurnet and Gutiérrez-Maldonado (2010) investigated a range of measures that may predict individual differences in experiences of presence.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the field of VR-based research geared toward clinical application is not a novelty, there is still no direct correspondence of presence and related factors to the level of induced emotional arousal. Although a reinforcing role of realism on the behavioral response is noted in Slater et al (2009) and in full body avatars in Gutiérrez-Maldonado et al (2009), in Volonte et al (2016) an opposite effect is reported. Furthermore, compared to alternatives.…”
Section: Introductionmentioning
confidence: 89%
“…17 Fourteen articles are quantitative research, 13,[21][22][23][24][25][26][27][28][29][30][31][32][33] and 1 mixed study 34 was conducted between the years of 2007 and 2020. Ten of the 14 quantitative studies are experimental, 13,[21][22][23]26,[29][30][31][32][33] and 2 are observational. 24,25 Studies included are from different disciplines such as health care, engineering, education, and business.…”
Section: Literature Retrieval and Data Collectionmentioning
confidence: 99%
“…Other researchers share the same views as Minsky that presence is the psychological and subjective experience of "being there," or the experience of being in one environment even when the person is physically in an another 23,30,[38][39][40][41] or in a mediated environment. 21,24,32,42 It is further considered as the feeling of being in a perceived external world around the self, and this view underlines the emerging of "presence" and "absence" as opposite poles of experience in our relation to the self and the other. Total presence is a complete absorption in the external world (the other).…”
Section: Other Definitions Of Presencementioning
confidence: 99%
See 1 more Smart Citation